Study of Lusi River Flood Discharge in Central Java Province - Pontjo Witjaksono Arief Rachmanto (Journal of the Civil Engineering Forum, 2013)
Lusi is one of the big rivers of Serang Lusi Juana (Seluna) River System that contributes to flood event on the downstream part of the system. To cope with the flood problem occurred in Seluna River System. Kedungombo Dam has been constructed on the upstream part of Serang River. However, flood flow from Lusi River, which covers 2.100 km2 of catchment area, cannot be controlled.By calculating the Lusi River design flood discharge, the flood discharge contribution of Lusi River to the Seluna River System can be predicted. Design flood hydrograph of Lusi River is determined using the synthetic unit hydrograph approach due to inadequate data. The synthetic unit hydrograph of Gama I is used in this study. To distribute design daily rainfall into hourly rainfall units to be applied in flood hydrograph calculation, hypothetic rainfall distribution is used by employing the Alternating Block Method (ABM) and Tadashi Tanimoto methods for several floods returning period.Design flood discharge applied for the calculation is the results of the ABM Rainfall distribution based on the two-daily rainfall data. The results of design flood discharge under this method show 748m3/s for return period of 2 years, 1036m3/s for return period of 50 years, 1097 m3/s for return period of 100 years and 1158 m3/s for return period of 200 years. 96% of Lusi River design flood gives contribution to the Seluna River System which is approximately 1200m3/s gained from Q200 design flood discharge in Klambu barrageKey Words: Flood discharge, synthetic unit hydrograph, hypothetical rainfall distribution, design discharge.